Superarse/Superarme: Os Paradoxos Da Liberdade No Trabalho Dos Imigrantes Na Indústria De Costura No Capitalismo Contemporâneo - Scavitti, Julia Ferreira [UNIFESP] (2017)
This Research Reflects The Relationship Between International Labor Migration And Dependency Theory And Superexploration Of Work Based On The Specific Reality Of Immigrants In The Apparel Industry Of São Paulo In The Last Three Decades. It Also Seeks To Reflect On The Ideological Transformations Arising From The Critical Scenario That Emerged In The 1970S, When The Economic Crisis Demanded A Profound Transformation Of The Capitalist Mode Of Production. The Central Objective Was To Understand The Paradoxes Of The Notion Of Freedom In A Society Under The Neoliberal Capitalist Logic, Manifested Through The Work Relations Of The Sewing And The Discourses Mobilized By The Immigrant Workers Of This Sector. For That, A Qualitative Methodology Was Used, In The Form Of In-Depth Interviews And Participant Observation, As Well As A Bibliographic Review On The Subject